Molecular docking, free energy calculations, ADMETox studies, DFT analysis, and dynamic simulations highlighting a chromene glycoside as a potential inhibitor of PknG in Mycobacterium tuberculosis - Alruwaili, Muharib; Elsaman, Tilal; Mohamed, Magdi Awadalla; Elderdery, Abozer Y.; Mills, Jeremy; Alruwaili, Yasir; Hamza, Siddiqa M. A.; Mekki, Salma Elhadi Ibrahim; Alotaibi, Hazim Abdullah; Alrowily, Maily J.; Althobiti, Maryam Musleh (Frontiers in Chemistry, 2025)
IntroductionTuberculosis (TB), caused by the Mycobacterium tuberculosis (M.tb), remains a serious medical concern globally. Resistant M.tb strains are emerging, partly because M.tb can survive within alveolar macrophages, resulting in persistent infection. Protein kinase G (PknG) is a mycobacterial virulence factor that promotes the survival of M.tb in macrophages. Targeting PknG could offer an opportunity to suppress the resistant M.tb strains.MethodsIn the present study, multiple computational tools were adopted to screen a library of 460,000 molecules for potential inhibitors of PknG of M.tb.Results and discussionsSeven Hits (1–7) were identified with binding affinities exceeding that of the reference compound (AX20017) towards the PknG catalytic domain. Next, the ADMETox studies were performed to identify the best hit with appropriate drug-like properties. The chromene glycoside (Hit 1) was identified as a potential PknG inhibitor with better pharmacokinetic and toxicity profiles rendering it a potential drug candidate. Furthermore, quantum computational analysis was conducted to assess the mechanical and electronic properties of Hit 1, providing guidance for further studies. Molecular dynamics simulations were also performed for Hit 1 against PknG, confirming the stability of its complex. In sum, the findings in the current study highlight Hit 1 as a lead with potential for development of drugs capable of treating resistant TB.